1965
DOI: 10.7589/0090-3558-1.4.55
|View full text |Cite
|
Sign up to set email alerts
|

Leptospiral Agglutinins In Sera from Southern Illinois Herpetofauna

Abstract: A totalof 84 amphibians and reptiles were collected in southern Illinois and cultured for leptospires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…Although research on the occurrence of Leptospira spp. in the species studied is still in the early stages, some studies (ANDREWS et al, 1965;DEZZUTTO et al, 2017;GLOSSER et al, 1974;GRIMM et al, 2015;OLIVEIRA et al, 2016) have indicated that chelonians can serve as possible reservoirs of these agents, showing high prevalence rates similar to those detected of the present study.…”
supporting
confidence: 80%
“…Although research on the occurrence of Leptospira spp. in the species studied is still in the early stages, some studies (ANDREWS et al, 1965;DEZZUTTO et al, 2017;GLOSSER et al, 1974;GRIMM et al, 2015;OLIVEIRA et al, 2016) have indicated that chelonians can serve as possible reservoirs of these agents, showing high prevalence rates similar to those detected of the present study.…”
supporting
confidence: 80%
“…Many domestic and wild mammals have been found to be either natural reservoirs or accidental hosts for several serotypes of Leptospira spp. However, non-mammalian animals such as those belonging to the herpetofauna (Andrews et al, 1965;Jobbins and Alexander, 2015) may play a role as reservoir hosts when considering the epidemiology (Glosser et al, 1974), transmission and persistence of Leptospira spp. (Jobbins and Alexander, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Specific agglutinins were also found to serotype canicola in C. picta serum. Agglutinins to parasitic leptospires in lower vertebrate sera have been reported by others (2,9,23,26). However, these agglutinins may not be related to antibody and may not be epidemiologically related.…”
Section: Discussionmentioning
confidence: 83%